LARANGAN MENIKAH SATU KAUM DALAM MASYARAKAT SUKU PEKAL DITINJAU DARI PERSPEKTIF ISLAM (STUDI KASUS DI KECAMATAN MALIN DEMAN KABUPATEN MUKOMUKO) - Devi Marlina (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
The purpose of this study is to know and analyze the marriage of one kaum  in Pekal society in Malin Deman  sub-district  of Mukomuko  regency  in banned and  to know  the  view of Islamic  law concerning the prohibition of marriage of one  people in Pekal  society  in Kecamatan Malin Deman  of Mukomuko  Regency. The results of the study showed that the prohibition of marrying one of the people in Pekal sub-district,  Malin Deman  sub-district  of Mukomuko  Regency,  due  to the relative nature  of the kinship relationship, is feared  to damage the  relationship of silaturrahim, it is feared  there  will be  marriage between siblings, consider one brothers and to decide which dunsanak ) which does  not, educate shame, and a strong conviction  that there will be a bad thing against the descent and view of Islamic law concerning the prohibition of marriage of one kaum  in Pekal tribe society in Malin Deman  sub-district  Mukomuko  regency  is not in accordance with Islamic law because one brother  not included in those  who are forbidden to be married according to the Qur’an and Sunnah.  Thus can be said marriage of one punishable people may (mubah).